2017
DOI: 10.1080/10408398.2014.967385
|View full text |Cite
|
Sign up to set email alerts
|

Dairy products and inflammation: A review of the clinical evidence

Abstract: Inflammation is a major biological process regulating the interaction between organisms and the environment, including the diet. Because of the increase in chronic inflammatory diseases, and in light of the immune-regulatory properties of breastfeeding, the ability of dairy products to modulate inflammatory processes in humans is an important but unresolved issue. Here, we report a systematic review of 52 clinical trials investigating inflammatory markers in relation to the consumption of dairy products. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 89 publications
8
121
2
7
Order By: Relevance
“…In human studies, tissue levels of rTFA, and especially tPA, are often used as a biomarker of dairy fat intake [48,49]. A systematic review of human clinical trials reported a beneficial impact of dairy products on inflammation, especially in subjects with metabolic disorders, while the impact in healthy subjects was either beneficial or neutral [50]. In the present work, rTFA exerted their anti-inflammatory action in cells stimulated with TNF-α.…”
Section: Discussionmentioning
confidence: 56%
“…In human studies, tissue levels of rTFA, and especially tPA, are often used as a biomarker of dairy fat intake [48,49]. A systematic review of human clinical trials reported a beneficial impact of dairy products on inflammation, especially in subjects with metabolic disorders, while the impact in healthy subjects was either beneficial or neutral [50]. In the present work, rTFA exerted their anti-inflammatory action in cells stimulated with TNF-α.…”
Section: Discussionmentioning
confidence: 56%
“…However, data suggest that dairy products do not exert adverse effects on CVD risk and low-grade inflammation [11][12][13][14][15]; some investigators even found a decreased level of inflammatory markers associated with the consumption of dairy products [16]. In this regard, Bordoni et al found that the anti-inflammatory properties were characteristic of both low-and high-fat dairy products [17], but a better understanding of the relationship between dairy protein, dairy fat, and chronic diseases is essential [18].…”
Section: Introductionmentioning
confidence: 96%
“…However, data suggest that dairy products do not exert adverse 45 effects on CVD risk and low-grade inflammation [11][12][13][14][15]; some investigators even found 46 a decreased level of inflammatory markers associated with the consumption of dairy products [16]. In this regard, Bordoni et al found that the anti-inflammatory properties 48 were characteristic of both low-and high-fat dairy products [17], but a better 49 understanding of the relationship between dairy protein, dairy fat, and chronic diseases 50 is essential [18].…”
mentioning
confidence: 97%